Morphological and molecular characteristics of Kudoa scomberomori (Myxosporea: Kudoidae) firstly foundfrom the muscles of info-pacific king mackerel Scomberomorus guttatus in Quang Binh province, Vietnam - Chinh, Nguyen Ngoc; Ngo, Ha Duy; Duc, Nguyen Huu; Linh, Nguyen Thuy; Doanh, Pham Ngoc (Academia Journal of Biology, 2017)
The genus Kudoa includes about 100 described species. In Vietnam, so far, only one species, Kudoa monodactyli, has been reported. During servey for parasites of marine fish in Quang Binh province, Vietnam in 2017, we found Myxozoan samples in 8 out of 15 Indo-Pacific king mackerel (Scomberomorus guttatus). They are identified as K. scomberomori based on the results of morphological and molecular analyses. A great number of individual spores form white pseudocysts with thin membrane within the muscle fibre. The pseudocysts were 0.1-0.3 × 0.4-0.7 mm. The shape of fresh spore like a flower petal. The spore of K. scomberomori was 6.65 ± 0.09 (6.53-6.76) µm in length, 7.42 ± 0.13 (7.29-7.58) µm in width and 6.55 ± 0.11 (6.40-6.65) µm in thickness. Each spore has six shell valves with same size. Each shell valve contained one polar capsule measuring 3.42 ± 0.09 (3.32-3.48) µm in length and 1.30 ± 0.14 (1.14-1.46) µm in width. This is the first report of K. scomberomori in Vietnam and Indo-Pacific king mackerel is recorded as a new host for this species. Citation: Nguyen Ngoc Chinh, Ha Duy Ngo, Nguyen Huu Duc, Nguyen Thuy Linh, Pham Ngoc Doanh, 2017. Morphological and molecular characteristics of Kudoa scomberomori (Myxosporea: Kudoidae) firstly foundfrom the muscles of info-pacific king mackerel Scomberomorus guttatus in Quang Binh province, Vietnam. Tap chi Sinh hoc, 40(1): x-xx. DOI: 10.15625/0866-7160/v40n1.10671. *Corresponding author: chinhnn89@gmail.com Received 13 September 2017, accepted 2 December 2017